KETIMPANGAN PENDAPATAN PROVINSI DI INDONESIA: ANALISIS DATA PANEL - Raudhatil Wirda Z.; Fakhruddin Fakhruddin; Fitriyani Fitriyani (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2020)
AbstractThe purpose of this study is to analyze income inequality in Indonesia at the provincial level. The variables used are the Gini index, inflation, the percentage of poor people, and economic growth. The model used is a regression panel for the period 2012-2018. Estimation results show that inflation has a negative and significant effect on income inequality, poverty has a positive and significant effect on income inequality, while economic growth has a positive but not significant effect on income inequality in Indonesia. Thus, the government should use inflation and poverty alleviation programs as instruments to reduce income inequality in Indonesia.